PVC (polyvinyl chloride) board with heat insulation, sound insulation and heat preservation functions
By grafting carbon dots on hollow glass microspheres and compounding them with carbon fibers, the composite filler CF-HGB-CDs@PAN is solved, and the PVC sheets are insufficient in thermal insulation and sound insulation performance are improved, and their anti-aging, anti-static and mechanical strength are suitable for outdoor environments.
Patent Information
- Application Number
- CN202510408748.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-02
- Publication Date
- 2025-07-18
AI Technical Summary
Existing PVC panels still need to be improved in terms of thermal insulation and sound insulation performance, and it is difficult to have these properties while also having aging resistance and anti-static properties, especially when used in outdoor environments.
By grafting carbon dots on hollow glass microspheres, forming load-modified glass microspheres, then compounding with carbon fibers, and coating them with polyaniline, the composite filler CF-HGB-CDs@PAN is prepared for the preparation of PVC plates to improve thermal insulation, sound insulation, anti-aging and anti-static properties.
It realizes that PVC sheets maintain excellent thermal insulation and sound insulation performance while having good anti-aging and anti-static properties, significantly improved mechanical strength and flame retardant properties, and are suitable for outdoor environments.
Smart Images

Figure CN120329666A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of PVC materials, and particularly to a PVC board with heat insulation, sound insulation and heat preservation functions. Background Art
[0002] PVC boards have the advantages of light weight, heat insulation, sound insulation, fire resistance, waterproofness, corrosion resistance, etc., making them widely used, such as being used as outdoor plastic building materials, indoor floor materials or other furniture materials, vehicle roof linings or interior decoration materials, equipment box materials, etc.
[0003] Using PVC boards with good heat insulation and sound insulation characteristics for the exterior walls and roof parts of buildings can effectively isolate factors such as high temperature, low temperature, and noise outdoors, improving the comfort of the interior. For example, a preparation method and application of a high heat-insulating, sound-insulating and weather-resistant PVCU profile disclosed in patent CN111070831B provides PVC materials with good heat insulation and sound insulation performance. In many application scenarios, in addition to having high requirements for the heat insulation and sound insulation performance of PVC boards, there are also certain requirements for their heat-oxidative aging and / or ultraviolet aging (especially when applied to outdoor environments), flame retardancy performance, etc. In some other application scenarios, such as being used for vehicle or equipment shells or indoor floor materials, etc., it is also desired to have certain antistatic performance, such as an antistatic and flame-retardant PVC board provided by patent CN114133678A.
[0004] Hollow glass microspheres have characteristics such as being hollow, light in weight, heat-insulating and heat-preserving, and having stable chemical properties, and also have good sound insulation ability (Shi Xuejun. Mechanical and Sound Insulation Properties of Epoxy Resin / Hollow Filler Composites. Diss. Huazhong University of Science and Technology.), making them widely used as inorganic fillers in polymer materials, such as being applied to PVC materials to improve the heat insulation and sound insulation performance of PVC. For example, a high-temperature resistant and high-toughness PVC-U double-wall corrugated pipe and its preparation method disclosed in patent CN104650501A. However, there are the following deficiencies in its application in polymer materials: (1) Hollow glass microspheres have a large polarity, are prone to agglomeration, and have poor compatibility with organic polymer materials, and cannot form a strong interfacial bonding force with the matrix (Chen Feng. Surface Graft Polymerization Modification of Hollow Glass Microspheres and Its Application in Polyurethane Composites. Diss. Nanjing University.); (2) The hollow structure of hollow glass microspheres results in insufficient mechanical strength, and when the addition amount is large, it is easy to have a negative impact on the mechanical strength of the polymer substrate (Yang Pengfei, Zhu Zhenguo, Zhang Jinxin. Preparation and Properties of Lightweight and High-Strength Thermal Insulation Composites [J]. Shandong Chemical Industry, 2020, 49(17): 13-16).
[0005] The heat insulation and sound insulation properties of traditional PVC sheets still need to be further improved. Moreover, it is usually very difficult to have both heat insulation and sound insulation characteristics while also having properties such as aging resistance and antistatic properties, which makes the application effect difficult to meet the requirements or limits their application.
[0006] Therefore, it is necessary to improve the existing technology to provide a more reliable solution. Summary of the Invention
[0007] The technical problem to be solved by the present invention is to provide a PVC board with heat insulation, sound insulation and heat preservation functions in view of the deficiencies in the above-mentioned prior art.
[0008] To solve the above technical problem, the technical solution adopted by the present invention is: a PVC board with heat insulation, sound insulation and heat preservation functions, and its preparation raw materials include, by weight: 100 parts of PVC resin powder, 10 - 23 parts of plasticizer, 2.5 - 6 parts of stabilizer, 1 - 3 parts of barite powder, 4 - 15 parts of maleic anhydride grafted polypropylene, and 3.5 - 10 parts of composite filler;
[0009] The composite filler is prepared through the following steps:
[0010] S1. Graft carbon dots on hollow glass microspheres to obtain load-modified glass microspheres: HGB-CDs;
[0011] S2. Compound HGB-CDs with carbon fiber to prepare glass microsphere-carbon fiber composite: CF-HGB-CDs;
[0012] S3. Coat CF-HGB-CDs with polyaniline to obtain composite filler: CF-HGB-CDs@PAN.
[0013] Preferably, step S1 is specifically as follows:
[0014] S1-1. Activation: Take hollow glass microspheres and add them to sodium hydroxide solution, stir for 2 - 8 h under heating, filter, wash the hollow glass microspheres with deionized water until neutral, and dry them under vacuum to obtain activated hollow glass microspheres;
[0015] S1-2. Take the activated hollow glass microspheres and add them to a mixed solution composed of deionized water and ethanol, add Cu(NO3)2, and disperse them ultrasonically to obtain mixture 1;
[0016] S1-3. Take lutein, tert-butylhydroquinone, citric acid, and ethylenediamine and add them to a mixed solution composed of deionized water and ethanol, and stir to obtain mixture 2;
[0017] S1-4. Under stirring, add mixture 2 to mixture 1, and disperse it by ultrasonic wave to obtain a precursor solution; transfer the precursor solution to a reaction kettle, react at 180 - 220 °C for 8 - 16 h, cool to room temperature after the reaction, filter by centrifugation, wash the solid product successively with deionized water and ethanol, and dry it under vacuum to obtain the loaded modified glass microspheres: HGB-CDs.
[0018] Preferably, step S1 is specifically as follows:
[0019] S1-1. Activation: Take 2 - 10 g of hollow glass microspheres and add them to 75 - 300 mL of sodium hydroxide solution with a concentration of 0.5 - 2 mol / L, stir at 70 - 95 °C for 2 - 8 h, filter, wash the hollow glass microspheres with deionized water until neutral, and dry them under vacuum at 60 - 90 °C for 6 - 24 h to obtain the activated hollow glass microspheres;
[0020] S1-2. Take 1 - 4 g of the activated hollow glass microspheres and add them to a mixed solution composed of 30 - 120 mL of deionized water and 70 - 250 mL of ethanol, add 0.188 - 0.752 g of Cu(NO3)2, and disperse it by ultrasonic wave for 30 - 90 min to obtain mixture 1;
[0021] S1-3. Take 142 - 570 mg of lutein, 83 - 332 mg of tert-butylhydroquinone, 192 - 768 mg of citric acid, and 22 - 90 mg of ethylenediamine and add them to a mixed solution composed of 15 - 60 mL of deionized water and 35 - 140 mL of ethanol, stir for 5 - 30 min to obtain mixture 2;
[0022] S1-4. Under stirring, add mixture 2 to mixture 1, and disperse it by ultrasonic wave for 15 - 45 min to obtain a precursor solution; transfer the precursor solution to a reaction kettle with a polytetrafluoroethylene inner liner, react at 180 - 220 °C for 8 - 16 h, cool to room temperature after the reaction, filter by centrifugation, wash the solid product successively with deionized water and ethanol, and dry it under vacuum at 70 - 100 °C for 6 - 24 h to obtain the loaded modified glass microspheres: HGB-CDs.
[0023] Preferably, step S2 is specifically as follows:
[0024] S2-1. Acylation treatment of HGB-CDs:
[0025] Take HGB-CDs and add them to thionyl chloride, then add N,N-dimethylformamide, disperse it by ultrasonic wave, stir and react under heating. After the reaction, filter, wash the solid product until neutral, and dry it under vacuum to obtain the acylated microspheres;
[0026] S2-2. Amination treatment of the acylated microspheres:
[0027] The acyl chloride microspheres are added to ethylenediamine, and then N,N-dimethylformamide is added. After ultrasonic dispersion, the reaction is stirred under heating. After the reaction is completed, filtration is carried out, and the solid product is washed to neutrality and dried under vacuum to obtain aminated microspheres;
[0028] S2-3. Acidification treatment of carbon fiber:
[0029] The carbon fiber is added to the mixed acid composed of 65 wt% concentrated nitric acid and 95 wt% concentrated sulfuric acid, stirred under heating, filtered, and the solid product is washed with deionized water to neutrality to obtain acidified carbon fiber;
[0030] S2-4. Acyl chloride treatment of acidified carbon fiber:
[0031] The acidified carbon fiber is added to thionyl chloride, and then N,N-dimethylformamide is added. After ultrasonic dispersion, filtration is carried out, and the solid product is washed to neutrality and dried under vacuum to obtain acyl chloride carbon fiber;
[0032] S2-5. Composite treatment:
[0033] The aminated microspheres and acyl chloride carbon fiber are added to N,N-dimethylformamide, ultrasonically dispersed, and then reacted under heating. After the reaction is completed, filtration is carried out, and the solid product is washed to neutrality and dried under vacuum to obtain glass microsphere-carbon fiber composite: CF-HGB-CDs.
[0034] Preferably, step S2 is specifically:
[0035] S2-1. Acyl chloride treatment of HGB-CDs:
[0036] 0.25 - 1 g of HGB-CDs is added to 150 - 700 mL of thionyl chloride, and then 25 - 100 mL of N,N-dimethylformamide is added. After ultrasonic dispersion for 15 - 60 min, the reaction is stirred at 70 - 85 °C for 12 - 48 h. Filtration is carried out, and the solid product is washed with acetone to neutrality and dried under vacuum at 70 - 95 °C for 6 - 24 h to obtain acyl chloride microspheres;
[0037] S2-2. Amination treatment of acyl chloride microspheres:
[0038] 0.1 - 0.4 g of acyl chloride microspheres is added to 75 - 300 ml of ethylenediamine, and then 5 - 20 mL of N,N-dimethylformamide is added. After ultrasonic dispersion for 15 - 60 min, the reaction is stirred at 70 - 90 °C for 24 - 72 h. Filtration is carried out, and the solid product is washed with acetone to neutrality and dried under vacuum at 70 - 90 °C for 6 - 24 h to obtain aminated microspheres;
[0039] S2-3. Acidification treatment of carbon fiber:
[0040] Take 0.25 - 1 g of carbon fiber and add it to 50 - 200 mL of a mixed acid composed of 65 wt% concentrated nitric acid and 95 wt% concentrated sulfuric acid in a volume ratio of 3:1. Stir at 50 - 70 °C for 2 - 8 h, filter, and wash the solid product with deionized water until neutral to obtain acidified carbon fiber;
[0041] S2 - 4. Acylation treatment of acidified carbon fiber:
[0042] Take 0.25 - 1 g of acidified carbon fiber and add it to 50 - 200 mL of thionyl chloride, then add 4 - 16 mL of N,N - dimethylformamide. Ultrasonically disperse for 5 - 20 min, filter, wash the solid product with acetone until neutral, and vacuum dry at 70 - 90 °C for 6 - 24 h to obtain acylated carbon fiber
[0043] S2 - 5. Composite treatment:
[0044] Take 0.1 - 0.4 g of aminated microspheres and 0.075 - 0.3 g of acylated carbon fiber and add them to 40 - 160 mL of N,N - dimethylformamide. Ultrasonically disperse for 30 - 90 min, then react at 65 - 85 °C for 18 - 72 h, filter, wash the solid product with acetone until neutral, and vacuum dry at 70 - 95 °C for 6 - 24 h to obtain glass microsphere - carbon fiber composite: CF - HGB - CDs.
[0045] Preferably, step S3 is specifically as follows:
[0046] S3 - 1. Take ammonium persulfate and add it to an aqueous hydrochloric acid solution, stir to obtain an ammonium persulfate solution;
[0047] S3 - 2. Take CF - HGB - CDs and aniline monomer and add them to an aqueous hydrochloric acid solution. Ultrasonically disperse, under nitrogen protection and continuous stirring, dropwise add the ammonium persulfate solution. After the addition is complete, keep stirring and continue the reaction. After the reaction ends, filter, wash the obtained solid product, and vacuum dry to obtain composite filler: CF - HGB - CDs@PAN.
[0048] Preferably, step S3 is specifically as follows:
[0049] S3 - 1. Take 2.25 - 9 g of ammonium persulfate and add it to 25 - 100 mL of an aqueous hydrochloric acid solution with a concentration of 0.5 - 2.0 mol / L. Stir for 2 - 10 min to obtain an ammonium persulfate solution;
[0050] S3-2: Take 0.5 - 2 g of CF-HGB-CDs and 0.9 - 3.6 g of aniline monomer, add them to 60 - 240 mL of hydrochloric acid aqueous solution with a concentration of 0.5 - 2 mol / L, ultrasonically disperse for 1 - 4 h, dropwise add ammonium persulfate solution under nitrogen protection, at 0 - 8 °C with continuous stirring. After the addition is completed, keep stirring and continue to react at 0 - 8 °C for 9 - 36 h. After the reaction is completed, filter, wash the obtained solid product successively with 0.01 mol / L hydrochloric acid and acetone, and vacuum dry at 70 - 90 °C for 6 - 24 h to obtain the composite filler: CF-HGB-CDs@PAN.
[0051] Preferably, the plasticizer is at least one of dioctyl terephthalate, dioctyl phthalate, diisononyl phthalate, trioctyl trimellitate, dioctyl oxalate, triisooctyl trimellitate, bis(2-propylheptyl) phthalate (DPHP).
[0052] Preferably, the stabilizer is at least one of calcium stearate, zinc stearate, calcium oleate, and zinc oleate.
[0053] Preferably, the PVC board with heat insulation, sound insulation and heat preservation functions is prepared by the following method:
[0054] Add the raw materials according to the formula components into a mixer, stir and knead at 100 - 125 °C and 300 - 800 rpm for 15 - 30 min, then add them into an open mill, open mill at 115 - 140 °C and 500 - 1000 rpm for 1 - 5 min. Add the obtained mixture into a screw extruder, melt and extrude at 180 - 200 °C. The extruded melt is calendered into shape by a calender, and after peeling and cooling to room temperature, a PVC board with heat insulation, sound insulation and heat preservation functions is obtained.
[0055] The beneficial effects of the present invention are:
[0056] The PVC board provided by the present invention not only has excellent heat insulation, heat preservation and sound insulation properties, but also has good anti-aging and anti-static properties, and has high mechanical strength and good flame retardancy, and has broad market application prospects;
[0057] In the present invention, by compounding hollow glass microspheres (HGB), carbon dots (CDs) and carbon fiber (CF), and then performing organic polymer modification with polyaniline, a composite filler CF-HGB-CDs@PAN with a composite structure system is obtained, which can significantly improve the heat insulation, sound insulation, flame retardant and anti-aging properties of PVC, while ensuring the mechanical strength of PVC and endowing it with good antistatic properties; by endowing the PVC board with excellent anti-ultraviolet aging and thermal-oxidative aging properties through the composite filler, it can be better applied to outdoor environments; by endowing the PVC board with antistatic properties, its application scenarios can be broadened.
[0058] In the composite filler CF-HGB-CDs@PAN of the present invention, the hollow glass microspheres can provide good heat insulation and sound insulation properties; the carbon fiber can improve the mechanical strength of PVC, compensate for the reduction in mechanical strength caused by adding hollow glass microspheres, and at the same time improve the flame retardant properties; the carbon dots have excellent antioxidant and anti-ultraviolet functions, and can endow PVC with good anti-aging properties; the coating of polyaniline can simultaneously solve the problem of poor compatibility between carbon fiber and hollow glass microspheres and the PVC resin system, and can also endow the PVC board with good antistatic properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] Figure 1 Infrared absorption spectrum of the loaded modified glass microspheres prepared in Example 1;
[0060] Figure 2 Ultraviolet-visible absorption spectrum of the loaded modified glass microspheres prepared in Example 1;
[0061] Figure 3 Test results of the antioxidant performance of the loaded modified glass microspheres prepared in Example 1;
[0062] Figure 4 Test results of the thermal conductivity of Examples and Comparative Examples;
[0063] Figure 5 Test results of the sound insulation performance of Examples and Comparative Examples;
[0064] Figure 6 Test results of the tensile strength of Examples and Comparative Examples;
[0065] Figure 7 Test results of the flame retardant performance of Examples and Comparative Examples;
[0066] Figure 8 Test results of the anti-aging performance of Examples and Comparative Examples. DETAILED DESCRIPTION OF THE INVENTION
[0067] The present invention will be further described in detail below in conjunction with embodiments, so that those skilled in the art can implement it with reference to the text of the specification.
[0068] It should be understood that the terms such as "having", "comprising", and "including" used herein do not exclude the presence or addition of one or more other elements or their combinations.
[0069] Unless otherwise specified, the test methods used in the following examples are all conventional methods. The materials and reagents used in the following examples can be obtained from commercial sources unless otherwise specified. For those not specified in the following examples, they are carried out under conventional conditions or conditions recommended by the manufacturer. For reagents or instruments without indicating the manufacturer, they are all conventional products that can be obtained through commercial purchase.
[0070] The present invention provides a PVC board with heat insulation, sound insulation and heat preservation functions, and its preparation raw materials include, by weight: 100 parts of PVC resin powder, 10-23 parts of plasticizer, 2.5-6 parts of stabilizer, 1-3 parts of barite powder, 4-15 parts of maleic anhydride grafted polypropylene, and 3.5-10 parts of composite filler;
[0071] The composite filler is prepared by the following steps:
[0072] S1. Graft carbon dots on hollow glass microspheres to obtain load-modified glass microspheres: HGB-CDs;
[0073] S1-1. Activation: Take 2-10 g of hollow glass microspheres and add them to 75-300 mL of sodium hydroxide solution with a concentration of 0.5-2 mol / L, stir at 70-95 °C for 2-8 h, filter, wash the hollow glass microspheres with deionized water until neutral, and vacuum dry at 60-90 °C for 6-24 h to obtain activated hollow glass microspheres;
[0074] S1-2. Take 1-4 g of activated hollow glass microspheres and add them to a mixed solution composed of 30-120 mL of deionized water and 70-250 mL of ethanol, add 0.188-0.752 g of Cu(NO3)2, and ultrasonically disperse for 30-90 min to obtain mixture 1;
[0075] S1-3. Take 142-570 mg of lutein, 83-332 mg of tert-butylhydroquinone, 192-768 mg of citric acid, and 22-90 mg of ethylenediamine and add them to a mixed solution composed of 15-60 mL of deionized water and 35-140 mL of ethanol, stir for 5-30 min to obtain mixture 2;
[0076] S1-4. Under stirring, add mixture 2 to mixture 1, and ultrasonically disperse for 15 - 45 min to obtain a precursor solution; transfer the precursor solution to a reaction kettle with a polytetrafluoroethylene inner lining, react at 180 - 220 °C for 8 - 16 h, cool to room temperature after the reaction, centrifuge and filter, wash the solid product successively with deionized water and ethanol, and vacuum dry at 70 - 100 °C for 6 - 24 h to obtain supported modified glass microspheres: HGB-CDs.
[0077] S2. Composite HGB-CDs with carbon fiber to prepare a glass microsphere-carbon fiber composite: CF-HGB-CDs;
[0078] S2-1. Acylation treatment of HGB-CDs:
[0079] Take 0.25 - 1 g of HGB-CDs and add it to 150 - 700 mL of thionyl chloride, then add 25 - 100 mL of N,N-dimethylformamide, ultrasonically disperse for 15 - 60 min, stir and react at 70 - 85 °C for 12 - 48 h, filter, wash the solid product with acetone until neutral, and vacuum dry at 70 - 95 °C for 6 - 24 h to obtain acylated microspheres;
[0080] S2-2. Amination treatment of acylated microspheres:
[0081] Take 0.1 - 0.4 g of acylated microspheres and add them to 75 - 300 ml of ethylenediamine, then add 5 - 20 mL of N,N-dimethylformamide, ultrasonically disperse for 15 - 60 min, stir and react at 70 - 90 °C for 24 - 72 h, filter, wash the solid product with acetone until neutral, and vacuum dry at 70 - 90 °C for 6 - 24 h to obtain aminated microspheres;
[0082] S2-3. Acidification treatment of carbon fiber:
[0083] Take 0.25 - 1 g of carbon fiber and add it to 50 - 200 mL of a mixed acid composed of 65 wt% concentrated nitric acid and 95 wt% concentrated sulfuric acid in a volume ratio of 3:1, stir at 50 - 70 °C for 2 - 8 h, filter, wash the solid product with deionized water until neutral to obtain acidified carbon fiber;
[0084] S2-4. Acylation treatment of acidified carbon fiber:
[0085] Take 0.25 - 1 g of acidified carbon fiber and add it to 50 - 200 mL of thionyl chloride, then add 4 - 16 mL of N,N-dimethylformamide, ultrasonically disperse for 5 - 20 min, filter, wash the solid product with acetone until neutral, and vacuum dry at 70 - 90 °C for 6 - 24 h to obtain acylated carbon fiber
[0086] S2-5. Composite treatment:
[0087] Take 0.1 - 0.4 g of aminated microspheres and 0.075 - 0.3 g of acyl chloride carbon fiber and add them to 40 - 160 mL of N,N - dimethylformamide. Ultrasonically disperse for 30 - 90 min, then react at 65 - 85 °C for 18 - 72 h. Filter, wash the solid product with acetone until neutral, and vacuum dry at 70 - 95 °C for 6 - 24 h to obtain a glass microsphere - carbon fiber composite: CF - HGB - CDs.
[0088] S3. Coat CF - HGB - CDs with polyaniline to obtain a composite filler: CF - HGB - CDs@PAN;
[0089] S3 - 1. Take 2.25 - 9 g of ammonium persulfate and add it to 25 - 100 mL of an aqueous hydrochloric acid solution with a concentration of 0.5 - 2.0 mol / L, stir for 2 - 10 min to obtain an ammonium persulfate solution;
[0090] S3 - 2. Take 0.5 - 2 g of CF - HGB - CDs and 0.9 - 3.6 g of aniline monomer and add them to 60 - 240 mL of an aqueous hydrochloric acid solution with a concentration of 0.5 - 2 mol / L. Ultrasonically disperse for 1 - 4 h, and drop - add the ammonium persulfate solution under nitrogen protection, at 0 - 8 °C, with continuous stirring. After the drop - addition is completed, keep stirring and continue to react at 0 - 8 °C for 9 - 36 h. After the reaction ends, filter, wash the obtained solid product with 0.01 mol / L hydrochloric acid and acetone in sequence, and vacuum dry at 70 - 90 °C for 6 - 24 h to obtain a composite filler: CF - HGB - CDs@PAN.
[0091] In a preferred embodiment, the plasticizer is at least one of dioctyl terephthalate, dioctyl phthalate, diisononyl phthalate, trioctyl trimellitate, dioctyl oxalate, triisooctyl trimellitate, bis(2 - propylheptyl) phthalate (DPHP). More preferably, the plasticizer is dioctyl terephthalate.
[0092] In a preferred embodiment, the stabilizer is at least one of calcium stearate, zinc stearate, calcium oleate, zinc oleate. More preferably, the stabilizer is calcium stearate.
[0093] In a preferred embodiment, the PVC board with heat - insulation, sound - insulation and heat - preservation functions is prepared by the following method:
[0094] Add the raw materials according to the formula components into a mixer, stir and knead at 100 - 125 °C and 300 - 800 rpm for 15 - 30 min, then add them into an open mill, open - mill at 115 - 140 °C and 500 - 1000 rpm for 1 - 5 min. Add the obtained mixture into a screw extruder, melt - extrude at 180 - 200 °C, and the extruded melt is calendered and formed by a calender. After peeling and cooling to room temperature, a PVC board with heat - insulation, sound - insulation and heat - preservation functions is obtained.
[0095] The composite filler of the present invention, CF-HGB-CDs@PAN, is a composite filling material obtained by compounding hollow glass microspheres (HGB), carbon dots (CDs) and carbon fibers (CF), and then subjecting them to organic polymer modification with polyaniline. It can significantly improve the heat insulation, sound insulation, flame retardancy and anti-aging properties of PVC, while ensuring the mechanical strength of PVC and endowing it with good antistatic properties.
[0096] In the composite filler CF-HGB-CDs@PAN, the hollow glass microspheres can provide good heat insulation and sound insulation performance; the carbon fibers can improve the mechanical strength of PVC, compensate for the reduction of mechanical strength caused by adding hollow glass microspheres, and at the same time improve the flame retardancy; the carbon dots have excellent antioxidant and anti-ultraviolet functions and can endow PVC with good anti-aging properties; the coating of polyaniline can simultaneously solve the problem of poor compatibility between carbon fibers and hollow glass microspheres and the PVC resin system, and can also endow the PVC board with good antistatic properties.
[0097] The main preparation mechanism and action mechanism of the composite filler CF-HGB-CDs@PAN are described below to facilitate the understanding of the present invention.
[0098] 1. Loading modification of hollow glass microspheres:
[0099] First, the hollow glass microspheres are soaked and activated with alkali solution. On the one hand, the impurities on their surface can be removed, and on the other hand, the hydroxyl content on their surface can be increased to facilitate subsequent grafting on their surface;
[0100] Then, using lutein, tert-butylhydroquinone, citric acid and ethylenediamine as the main raw materials, and Cu(NO3)2 as the metal doping component, carbon dots with reducibility are in-situ synthesized on the surface of the activated hollow glass microspheres by a one-pot hydrothermal method. The hydrothermally synthesized carbon dots are in-situ deposited on the surface of the hollow glass microspheres to achieve the loading modification of the hollow glass microspheres; Cu in the raw materials 2+ can promote the uniform and large-scale deposition of carbon dots on the surface of the hollow glass microspheres. The reason is that during the reaction process, Cu(NO3)2 is first mixed with the dispersion of hollow glass microspheres, and Cu 2+ is evenly connected to the surface of the hollow glass microspheres through coordination and electrostatic adsorption with hydroxyl groups, and then Cu 2+ also undergoes coordination and electrostatic adsorption with functional groups (carboxyl, hydroxyl, amino, etc.) in lutein, tert-butylhydroquinone, citric acid and ethylenediamine, so that the carbon dots synthesized during the hydrothermal reaction are evenly connected to the surface of the hollow glass microspheres by means of the bridging effect of Cu 2+ .
[0101] Among them, the synthesized carbon dots have abundant functional groups such as carboxyl, amino, and hydroxyl groups on their surfaces. They well inherit the reducibility of tert-butylhydroquinone and lutein, possess good antioxidant ability, and can effectively absorb and convert ultraviolet light, having excellent ultraviolet resistance. The combination of antioxidant and ultraviolet resistance can significantly improve the ultraviolet aging resistance and thermal-oxidative aging resistance of PVC. The doping of Cu can play a bridging role during the synthesis process. On the other hand, the doping of Cu into carbon dots can increase the electron cloud density, change the energy band structure of carbon dots, improve the light absorption and conversion efficiency of carbon dots, and contribute to enhancing the ultraviolet resistance of carbon dots.
[0102] 2. Composite of loaded and modified glass microspheres HGB-CDs and carbon fiber:
[0103] First, HGB-CDs are successively subjected to conventional acyl chlorination treatment (the abundant carboxyl functional groups on the carbon dots are replaced by acyl chloride functional groups to generate acyl chloride functional groups) and amination treatment (nucleophilic substitution reaction between amino groups and acyl chloride groups to introduce amino functional groups and achieve amine functionalization) to obtain aminated microspheres. Then, a similar method is used to perform acyl chlorination treatment on the acid-modified carbon fiber to obtain acyl chlorinated carbon fiber. Finally, the aminated microspheres and acyl chlorinated carbon fiber are blended, and the amino functional groups of the aminated microspheres react with the acyl chloride groups on the surface of the acyl chlorinated carbon fiber through nucleophilic substitution reaction, so that HGB-CDs are grafted onto the surface of the carbon fiber, and finally the glass microsphere-carbon fiber composite: CF-HGB-CDs is obtained.
[0104] Carbon fiber has excellent mechanical strength. Its composite with HGB-CDs can make up for the loss of mechanical strength caused by the addition of hollow glass microspheres. Carbon fiber can also improve the flame retardancy of the PVC substrate by acting as a barrier through high-temperature carbonization. In addition, carbon fiber has excellent thermal stability, can improve the thermal stability of PVC, and can improve the thermal-oxidative aging resistance of PVC in synergy with carbon dots. The hollow glass microspheres are grafted onto the carbon fiber, and the hollow glass microspheres can act as network nodes to promote the formation of a network structure of carbon fiber, thereby further enhancing the improvement effect of carbon fiber on mechanical strength.
[0105] 3. Coating of polyaniline:
[0106] Finally, the present invention uses polyaniline to perform surface modification and coating on the glass microsphere-carbon fiber composite to obtain the final composite filler. For its coating mechanism, the carbon fibers and carbon dots of the glass microsphere-carbon fiber composite contain abundant carboxyl and hydroxyl groups. These carboxyl and hydroxyl groups can form polyaniline in situ during the polymerization of aniline, and the polyaniline is coated on the surface of the glass microsphere-carbon fiber composite in a chemical bonding manner (Yu Dongxiu, et al. "Mechanism and dispersion stability of polyaniline-coated short carbon fibers." Journal of South China University of Technology: Natural Science Edition 35.7 (2007): 6.). The coating of polyaniline can improve the surface roughness of the glass microsphere-carbon fiber composite, greatly improve the compatibility of hollow glass microspheres, carbon fibers and the PVC resin system, and enhance the adhesion between the filler and the resin substrate, so as to better exert the multi-effect improvement effect of the glass microsphere-carbon fiber composite on the performance of the PVC resin system.
[0107] The above is the overall concept of the present invention. The following provides detailed examples and comparative examples on this basis to further illustrate the present invention.
[0108] The sources of the main raw materials in the following examples and comparative examples are shown in Table 1 below:
[0109] Table 1
[0110]
[0111] Example 1
[0112] A PVC board with heat insulation, sound insulation and heat preservation functions, the preparation raw materials of which include, by weight: 100 parts of PVC resin powder, 14 parts of plasticizer, 3 parts of stabilizer, 1.5 parts of barite powder, 12 parts of maleic anhydride grafted polypropylene, and 8 parts of composite filler.
[0113] This PVC board is prepared by the following method:
[0114] The raw materials are added to a mixer according to the formula components, stirred and kneaded at 110 °C and 500 rpm for 20 min, then added to an open mill, kneaded at 125 °C and 750 rpm for 3 min. The obtained mixture is added to a screw extruder and melt-extruded at 190 °C. The extruded melt is calendered and formed by a calender, and after peeling and cooling to room temperature, a PVC board with heat insulation, sound insulation and heat preservation functions is obtained.
[0115] In this example, the plasticizer is dioctyl terephthalate and the stabilizer is calcium stearate.
[0116] The composite filler is prepared by the following steps:
[0117] S1. Graft carbon dots on hollow glass microspheres to obtain load-modified glass microspheres:
[0118] S1-1. Activation: Take 5 g of hollow glass microspheres with a particle size of 5 - 50 μm and add them to 150 mL of a sodium hydroxide solution with a concentration of 1 mol / L. Stir at 90 °C for 4 h, filter, wash the hollow glass microspheres with deionized water until neutral, and vacuum dry at 70 °C for 12 h to obtain activated hollow glass microspheres;
[0119] S1-2. Take 2 g of the activated hollow glass microspheres and add them to a mixed solution composed of 60 mL of deionized water and 140 mL of ethanol. Add 0.376 g of Cu(NO3)2 and ultrasonically disperse for 60 min to obtain Mixture 1;
[0120] S1-3. Take 285 mg of lutein, 166 mg of tert-butylhydroquinone, 384 mg of citric acid, and 45 mg of ethylenediamine and add them to a mixed solution composed of 30 mL of deionized water and 70 mL of ethanol. Stir for 15 min to obtain Mixture 2;
[0121] S1-4. Under stirring, add Mixture 2 to Mixture 1 and ultrasonically disperse for 30 min to obtain a precursor solution; transfer the precursor solution to a reaction kettle with a polytetrafluoroethylene inner lining and react at 180 - 220 °C for 12 h. After the reaction, cool to room temperature, centrifuge and filter. Wash the solid product with deionized water and ethanol successively, and vacuum dry at 90 °C for 12 h to obtain loaded modified glass microspheres.
[0122] S2. Composite HGB-CDs with carbon fiber to prepare a glass microsphere - carbon fiber composite:
[0123] S2-1. Acyl chlorination treatment of HGB-CDs:
[0124] Take 0.5 g of HGB-CDs and add them to 350 mL of thionyl chloride, then add 50 mL of N,N-dimethylformamide. Ultrasonically disperse for 30 min and stir and react at 75 °C for 24 h. Filter, wash the solid product with acetone until neutral, and vacuum dry at 80 °C for 12 h to obtain acyl chlorinated microspheres;
[0125] S2-2. Amination treatment of acyl chlorinated microspheres:
[0126] Take 0.2 g of acyl chlorinated microspheres and add them to 150 ml of ethylenediamine, then add 10 mL of N,N-dimethylformamide. Ultrasonically disperse for 30 min and stir and react at 80 °C for 48 h. Filter, wash the solid product with acetone until neutral, and vacuum dry at 80 °C for 12 h to obtain aminated microspheres;
[0127] S2-3. Acidification treatment of carbon fiber:
[0128] Take 0.5 g of carbon fiber and add it to 100 mL of a mixed acid composed of 65 wt% concentrated nitric acid and 95 wt% concentrated sulfuric acid in a volume ratio of 3:1. Stir at 60 °C for 4 h, filter, and wash the solid product with deionized water until neutral to obtain acidified carbon fiber;
[0129] S2-4. Acylation treatment of acidified carbon fiber:
[0130] Take 0.5 g of acidified carbon fiber and add it to 100 mL of thionyl chloride, then add 8 mL of N,N-dimethylformamide. Ultrasonically disperse for 10 min, filter, and wash the solid product with acetone until neutral. Vacuum dry at 80 °C for 12 h to obtain acylated carbon fiber
[0131] S2-5. Composite treatment:
[0132] Take 0.2 g of aminated microspheres and 0.15 g of acylated carbon fiber and add them to 80 mL of N,N-dimethylformamide. Ultrasonically disperse for 45 min, then react at 75 °C for 36 h. Filter, wash the solid product with acetone until neutral, and vacuum dry at 80 °C for 12 h to obtain glass microsphere-carbon fiber composite: CF-HGB-CDs.
[0133] S3. Conduct polyaniline coating on CF-HGB-CDs to obtain composite filler:
[0134] S3-1. Take 4.5 g of ammonium persulfate and add it to 50 mL of a 1.0 mol / L hydrochloric acid aqueous solution. Stir for 5 min to obtain an ammonium persulfate solution;
[0135] S3-2. Take 1 g of CF-HGB-CDs and 1.8 g of aniline monomer and add them to 120 mL of a 1.0 mol / L hydrochloric acid aqueous solution. Ultrasonically disperse for 2 h, and under nitrogen protection, at 5 °C, continuously stir and dropwise add the ammonium persulfate solution. After the addition is complete, continue stirring and react at 5 °C for 18 h. After the reaction is completed, filter, and wash the obtained solid product with 0.01 mol / L hydrochloric acid and acetone in sequence. Vacuum dry at 75 °C for 12 h to obtain composite filler: CF-HGB-CDs@PAN.
[0136] Example 2
[0137] A PVC board with heat insulation, sound insulation, and heat preservation functions, the preparation raw materials of which include, by weight: 100 parts of PVC resin powder, 14 parts of plasticizer, 3 parts of stabilizer, 1.5 parts of barite powder, 12 parts of maleic anhydride grafted polypropylene, and 7 parts of composite filler.
[0138] The rest is the same as in Example 1.
[0139] Example 3
[0140] A PVC board with heat insulation, sound insulation and heat preservation functions, the preparation raw materials of which include, by weight: 100 parts of PVC resin powder, 15 parts of plasticizer, 3 parts of stabilizer, 1.2 parts of barite powder, 11 parts of maleic anhydride grafted polypropylene, and 8.5 parts of composite filler.
[0141] This PVC board is prepared by the following method:
[0142] Add the raw materials according to the formula components into a kneader, stir and knead at 120 °C and 600 rpm for 20 min, then add them into an open mill, open mill at 130 °C and 750 rpm for 4 min, add the obtained mixture into a screw extruder, melt and extrude at 190 °C, and the extruded melt is calendered and formed by a calender. After peeling and cooling to room temperature, a PVC board with heat insulation, sound insulation and heat preservation functions is obtained.
[0143] The rest is the same as in Example 1.
[0144] Comparative Example 1
[0145] This example is basically the same as Example 1, the difference is that:
[0146] The preparation raw materials of this example include, by weight: 100 parts of PVC resin powder, 14 parts of dioctyl terephthalate, 3 parts of calcium stearate, 1.5 parts of barite powder, 12 parts of maleic anhydride grafted polypropylene, 3.5 parts of hollow glass microspheres, and 3 parts of carbon fiber.
[0147] Comparative Example 2
[0148] This example is basically the same as Example 1, the difference is that:
[0149] The composite filler in this example is prepared by the following steps:
[0150] S1. Take 5 g of hollow glass microspheres with a particle size of 5 - 50 μm and add them to 150 mL of sodium hydroxide solution with a concentration of 1 mol / L, stir at 90 °C for 4 h, filter, wash the hollow glass microspheres with deionized water until neutral, and vacuum dry at 70 °C for 12 h to obtain activated hollow glass microspheres;
[0151] S2. Take 4.5 g of ammonium persulfate and add it to 50 mL of hydrochloric acid aqueous solution with a concentration of 1.0 mol / L, stir for 5 min to obtain an ammonium persulfate solution;
[0152] S3. Take 1 g of the activated hollow glass microspheres and 1.8 g of aniline monomer, add them to 120 mL of a hydrochloric acid aqueous solution with a concentration of 1.0 mol / L, ultrasonically disperse for 2 h, under nitrogen protection, at 5 °C, continuously stir and dropwise add ammonium persulfate solution. After the addition is completed, keep stirring and continue the reaction at 5 °C for 18 h. After the reaction is completed, filter, wash the obtained solid product successively with 0.01 mol / L hydrochloric acid and acetone, and vacuum dry at 75 °C for 12 h to obtain the composite filler.
[0153] Comparative Example 3
[0154] This example is basically the same as Example 1, except that:
[0155] The composite filler in this example is prepared through the following steps:
[0156] S1. Graft carbon dots onto the hollow glass microspheres to obtain the loaded and modified glass microspheres:
[0157] S1-1. Activation: Take 5 g of hollow glass microspheres with a particle size of 5 - 50 μm and add them to 150 mL of a sodium hydroxide solution with a concentration of 1 mol / L, stir at 90 °C for 4 h, filter, wash the hollow glass microspheres with deionized water until neutral, and vacuum dry at 70 °C for 12 h to obtain the activated hollow glass microspheres;
[0158] S1-2. Take 2 g of the activated hollow glass microspheres and add them to a mixed solution composed of 60 mL of deionized water and 140 mL of ethanol, ultrasonically disperse for 60 min to obtain Mixture 1;
[0159] S1-3. Take 285 mg of lutein, 166 mg of tert-butylhydroquinone, 384 mg of citric acid, and 45 mg of ethylenediamine and add them to a mixed solution composed of 30 mL of deionized water and 70 mL of ethanol, stir for 15 min to obtain Mixture 2;
[0160] S1-4. Under stirring, add Mixture 2 to Mixture 1, ultrasonically disperse for 30 min to obtain the precursor solution; transfer the precursor solution to a reaction kettle with a polytetrafluoroethylene inner lining, react at 180 - 220 °C for 12 h, after the reaction is completed, cool to room temperature, centrifuge and filter, wash the solid product successively with deionized water and ethanol, and vacuum dry at 90 °C for 12 h to obtain the loaded and modified glass microspheres.
[0161] S2 and S3 are the same as those in Example 1.
[0162] Comparative Example 4
[0163] This example is basically the same as Example 1, except that:
[0164] The composite filler in this example is prepared through the following steps:
[0165] S1. Graft carbon dots onto hollow glass microspheres to obtain loaded and modified glass microspheres. The specific steps are the same as those in Example 1;
[0166] S2. Coat the loaded and modified glass microspheres with polyaniline to obtain a composite filler:
[0167] S2-1. Take 4.5 g of ammonium persulfate and add it to 50 mL of a hydrochloric acid aqueous solution with a concentration of 1.0 mol / L, and stir for 5 min to obtain an ammonium persulfate solution;
[0168] S2-2. Take 1 g of the loaded and modified glass microspheres and 1.8 g of aniline monomer, add them to 120 mL of a hydrochloric acid aqueous solution with a concentration of 1.0 mol / L, ultrasonically disperse for 2 h, and dropwise add the ammonium persulfate solution under nitrogen protection, at 5 °C, with continuous stirring. After the addition is complete, keep stirring and continue the reaction at 5 °C for 18 h. After the reaction is completed, filter, wash the obtained solid product successively with 0.01 mol / L hydrochloric acid and acetone, and vacuum dry at 75 °C for 12 h to obtain the composite filler.
[0169] Comparative Example 5
[0170] This example is basically the same as Example 1, except that: in this example, the glass microsphere-carbon fiber composite CF-HGB-CDs prepared in Example 1 is used as the composite filler.
[0171] The products prepared in the examples and comparative examples are subjected to the following performance tests and characterizations to further illustrate the present invention.
[0172] I. Performance characterization:
[0173] (1) Refer to Figure 1 , which is the infrared absorption spectrum of the loaded and modified glass microspheres prepared in Example 1, indicating that carbon dots have been successfully grafted onto the hollow glass microspheres;
[0174] (2) Refer to Figure 2 , which is the ultraviolet-visible absorption spectrum of the loaded and modified glass microspheres prepared in Example 1, and it can be seen that it has a strong absorption in the ultraviolet light band;
[0175] (3) Antioxidant performance test:
[0176] The antioxidant performance of the loaded and modified glass microspheres prepared in Example 1 is tested using a nitrogen radical (DPPH) scavenging ability test kit. The specific method is: prepare a microsphere dispersion with a concentration of 0.2 mg / mL of the loaded and modified glass microspheres prepared in Example 1 using ethanol, and then use a DPPH scavenging ability test kit (visible spectrophotometry, Shanghai Shangbao Biotechnology Co., Ltd., BA1870) to detect the absorbance of the microsphere dispersion within a certain period of time to characterize its antioxidant performance.
[0177] Measurement principle:
[0178] DPPH free radical is a very stable nitrogen-centered free radical and one of the important indicators of the antioxidant capacity of a sample. DPPH free radical has a single electron, and its alcohol solution is purple with a strong absorption at 515 nm. When there is an antioxidant present, the DPPH free radical is scavenged, the color of its solution becomes lighter, and the absorbance at 515 nm decreases. Within a certain range, the change in absorbance is proportional to the degree of scavenging of the free radical. The ability of the sample to scavenge DPPH free radical is reflected by the degree of decrease in absorbance, that is, the more the absorbance decreases, the stronger the antioxidant capacity.
[0179] Figure 3 The test results show that the loaded modified glass microspheres have excellent antioxidant capacity.
[0180] II. Performance tests
[0181] The PVC boards prepared in the examples and comparative examples were subjected to the following performance tests.
[0182] 1. Heat insulation performance
[0183] The thermal conductivity was tested in accordance with the standard GB / T 11205 - 2009, and the test results are shown in the following table and Figure 4 as follows:
[0184]
[0185] 2. Sound insulation performance
[0186] The sound insulation performance was tested in accordance with the standard GB / T 19889.10 - 2006 "Acoustics - Measurement of sound insulation in buildings and building elements", and the test results are shown in the following table and Figure 5 as follows:
[0187]
[0188] Note: The above sound insulation coefficient results are the arithmetic mean of the sound insulation coefficients at the mid - frequencies of 250 Hz, 500 Hz, 1000 Hz, and 2000 Hz.
[0189] 3. Tensile strength
[0190] The tensile performance was tested in accordance with the standard GB / T 1040.1 - 2018. The dimensions of the PVC board specimen were 100 mm × 50 mm × 5 mm, and the test results are shown in the following table and Figure 6 as follows:
[0191]
[0192] 4. Surface resistance test
[0193] Tested according to the standard GB / T 1410-2006, the surface resistance of the PVC board specimens was measured using an insulation resistance tester (ZC90G) (the specimens were pre-treated for 24 h at a temperature of 25 °C and a relative humidity of 50% before testing), and the test voltage was 120 V. The test results are shown in the following table:
[0194]
[0195]
[0196] 5. Flame retardancy
[0197] The oxygen index was tested according to the standard GB / T 2406.2-2009, and the test results are shown in the following table and Figure 7 as follows:
[0198]
[0199] 6. Anti-aging performance
[0200] Referring to the standard GB / T 14522-2008 "Artificial weathering test method for plastics, coatings and rubber materials used in mechanical industrial products - Fluorescent ultraviolet lamp", thermal oxygen aging and ultraviolet aging tests were carried out. Thermal oxygen aging test conditions: 100 °C, 72 h; Ultraviolet aging test conditions: Ultraviolet aging test was carried out under an ultraviolet lamp with a wavelength of 254 nm and an illumination intensity of 4 mW / cm2, the specimen was 20 cm away from the lamp tube, and the irradiation time was 72 h. The test results are shown in the following table and Figure 8 as follows:
[0201]
[0202] It can be seen from the above test results that the PVC prepared in Examples 1-3 has excellent heat insulation and sound insulation performance, and also has good anti-aging and anti-static performance, and its mechanical strength is high and the flame retardancy is good;
[0203] In Comparative Example 1, hollow glass microspheres and carbon fibers were directly added to replace the composite filler, and all properties showed a significant decline;
[0204] In Comparative Example 2, carbon dots and carbon fibers were not added, and the antioxidant performance, flame retardancy and mechanical strength decreased significantly;
[0205] In Comparative Example 3, the carbon dots in the composite filler were not doped with copper, and the antioxidant performance decreased significantly;
[0206] In Comparative Example 4, carbon fibers were not added to the composite filler, and the mechanical properties and flame retardancy decreased significantly;
[0207] In Comparative Example 5, since polyaniline coating was not carried out, the dispersion of the filler in the PVC system was affected, and the comprehensive properties also decreased to varying degrees.
[0208] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and embodiments. It can be fully applied to various fields suitable for the present invention. For those familiar with the field, additional modifications can be easily made. Therefore, without departing from the general concept defined by the claims and the equivalent scope, the present invention is not limited to specific details.
Claims
1. A PVC board with heat insulation, sound insulation and heat preservation functions, characterized in that, The raw materials for its preparation include, by weight: 100 parts of PVC resin powder, 10 - 23 parts of plasticizer, 2.5 - 6 parts of stabilizer, 1 - 3 parts of barite powder, 4 - 15 parts of maleic anhydride grafted polypropylene, and 3.5 - 10 parts of composite filler; The composite filler is prepared through the following steps: S1. Graft carbon dots onto hollow glass microspheres to obtain load-modified glass microspheres: HGB-CDs; S2. Composite HGB-CDs with carbon fiber to prepare glass microsphere-carbon fiber composite: CF-HGB-CDs; S3. Coating CF-HGB-CDs with polyaniline to obtain composite filler: CF-HGB-CDs@PAN.
2. The PVC board with heat insulation, sound insulation and heat preservation functions according to claim 1, wherein, Step S1 is specifically as follows: S1-1. Activation: Take hollow glass microspheres and add them to sodium hydroxide solution, stir for 2 - 8 h under heating, filter, wash the hollow glass microspheres with deionized water until neutral, and vacuum dry to obtain activated hollow glass microspheres; S1-2. Take the activated hollow glass microspheres and add them to a mixed solution composed of deionized water and ethanol, add Cu(NO3)2, and ultrasonically disperse to obtain mixture 1; S1-3. Take lutein, tert-butylhydroquinone, citric acid, and ethylenediamine and add them to a mixed solution composed of deionized water and ethanol, stir to obtain mixture 2; S1-4. Under stirring, add mixture 2 to mixture 1, ultrasonically disperse to obtain a precursor solution; transfer the precursor solution to a reaction kettle, react at 180 - 220 °C for 8 - 16 h, cool to room temperature after the reaction, centrifuge and filter, wash the solid product with deionized water and ethanol in sequence, and vacuum dry to obtain load-modified glass microspheres: HGB-CDs.
3. The PVC board with heat insulation, sound insulation and heat preservation functions according to claim 2, characterized in that, Step S1 is specifically as follows: S1-1. Activation: Take 2 - 10 g of hollow glass microspheres and add them to 75 - 300 mL of sodium hydroxide solution with a concentration of 0.5 - 2 mol / L, stir at 70 - 95 °C for 2 - 8 h, filter, wash the hollow glass microspheres with deionized water until neutral, and vacuum dry at 60 - 90 °C for 6 - 24 h to obtain activated hollow glass microspheres; S1-2. Take 1 - 4 g of activated hollow glass microspheres and add them to a mixed solution composed of 30 - 120 mL of deionized water and 70 - 250 mL of ethanol, add 0.188 - 0.752 g of Cu(NO3)2, and ultrasonically disperse for 30 - 90 min to obtain mixture 1; S1-3. Take 142 - 570 mg of lutein, 83 - 332 mg of tert-butylhydroquinone, 192 - 768 mg of citric acid, and 22 - 90 mg of ethylenediamine and add them to a mixed solution composed of 15 - 60 mL of deionized water and 35 - 140 mL of ethanol, stir for 5 - 30 min to obtain mixture 2; S1-4. Under stirring, add Mixture 2 to Mixture 1, and ultrasonically disperse for 15 - 45 min to obtain a precursor solution; transfer the precursor solution to a reaction kettle lined with polytetrafluoroethylene, react at 180 - 220 °C for 8 - 16 h, cool to room temperature after the reaction, centrifuge and filter, wash the solid product successively with deionized water and ethanol, and vacuum dry at 70 - 100 °C for 6 - 24 h to obtain supported modified glass microspheres: HGB-CDs.
4. The PVC board with heat insulation, sound insulation and heat preservation functions according to claim 1, characterized in that, Step S2 is specifically as follows: S2-1. Acylation treatment of HGB-CDs: Take HGB-CDs and add them to thionyl chloride, then add N,N-dimethylformamide, ultrasonically disperse, stir and react under heating. After the reaction, filter, wash the solid product until neutral, and vacuum dry to obtain acylated microspheres; S2-2. Amination treatment of acylated microspheres: Take the acylated microspheres and add them to ethylenediamine, then add N,N-dimethylformamide, ultrasonically disperse, stir and react under heating. After the reaction, filter, wash the solid product until neutral, and vacuum dry to obtain aminated microspheres; S2-3. Acidification treatment of carbon fiber: Take carbon fiber and add it to a mixed acid composed of 65 wt% concentrated nitric acid and 95 wt% concentrated sulfuric acid, stir under heating, filter, and wash the solid product with deionized water until neutral to obtain acidified carbon fiber; S2-4. Acylation treatment of acidified carbon fiber: Take the acidified carbon fiber and add it to thionyl chloride, then add N,N-dimethylformamide, ultrasonically disperse, filter, wash the solid product until neutral, and vacuum dry to obtain acylated carbon fiber; S2-5. Composite treatment: Take the aminated microspheres and acylated carbon fiber and add them to N,N-dimethylformamide, ultrasonically disperse, and then react under heating. After the reaction, filter, wash the solid product until neutral, and vacuum dry to obtain a glass microsphere-carbon fiber composite: CF-HGB-CDs.
5. The PVC board with heat insulation, sound insulation and heat preservation functions according to claim 4, characterized in that, Step S2 is specifically as follows: S2-1. Acylation treatment of HGB-CDs: Take 0.25 - 1 g of HGB-CDs and add them to 150 - 700 mL of thionyl chloride, then add 25 - 100 mL of N,N-dimethylformamide, ultrasonically disperse for 15 - 60 min, stir and react at 70 - 85 °C for 12 - 48 h, filter, wash the solid product with acetone until neutral, and vacuum dry at 70 - 95 °C for 6 - 24 h to obtain acylated microspheres; S2-2. Amination treatment of acylated microspheres: Take 0.1 - 0.4 g of acylated microspheres and add them to 75 - 300 ml of ethylenediamine, then add 5 - 20 mL of N,N-dimethylformamide, ultrasonically disperse for 15 - 60 min, stir and react at 70 - 90 °C for 24 - 72 h, filter, wash the solid product with acetone until neutral, and vacuum dry at 70 - 90 °C for 6 - 24 h to obtain aminated microspheres; S2-3. Acidification treatment of carbon fiber: Take 0.25 - 1 g of carbon fiber and add it to 50 - 200 mL of a mixed acid composed of 65 wt% concentrated nitric acid and 95 wt% concentrated sulfuric acid in a volume ratio of 3:1, stir at 50 - 70 °C for 2 - 8 h, filter, and wash the solid product with deionized water until neutral to obtain acidified carbon fiber; S2-4. Acylation treatment of acidified carbon fiber: Add 0.25 - 1 g of acidified carbon fiber to 50 - 200 mL of thionyl chloride, then add 4 - 16 mL of N,N-dimethylformamide, ultrasonically disperse for 5 - 20 min, filter, wash the solid product with acetone until neutral, and vacuum dry at 70 - 90 °C for 6 - 24 h to obtain acylated carbon fiber. S2-5. Composite treatment: Take 0.1 - 0.4 g of aminated microspheres and 0.075 - 0.3 g of acylated carbon fiber and add them to 40 - 160 mL of N,N-dimethylformamide, ultrasonically disperse for 30 - 90 min, then react at 65 - 85 °C for 18 - 72 h, filter, wash the solid product with acetone until neutral, and vacuum dry at 70 - 95 °C for 6 - 24 h to obtain glass microsphere-carbon fiber composite: CF-HGB-CDs.
6. The PVC board with heat insulation, sound insulation and heat preservation functions according to claim 1, characterized in that, Step S3 is specifically as follows: S3-1. Take ammonium persulfate and add it to hydrochloric acid aqueous solution, stir to obtain ammonium persulfate solution. S3-2. Take CF-HGB-CDs and aniline monomer and add them to hydrochloric acid aqueous solution, ultrasonically disperse, under nitrogen protection and continuous stirring, dropwise add ammonium persulfate solution. After the addition is completed, keep stirring and continue the reaction. After the reaction ends, filter, wash the obtained solid product, and vacuum dry to obtain composite filler: CF-HGB-CDs@PAN.
7. The PVC board with heat insulation, sound insulation and heat preservation functions according to claim 6, wherein, Step S3 is specifically as follows: S3-1. Take 2.25 - 9 g of ammonium persulfate and add it to 25 - 100 mL of hydrochloric acid aqueous solution with a concentration of 0.5 - 2.0 mol / L, stir for 2 - 10 min to obtain ammonium persulfate solution. S3-2. Take 0.5 - 2 g of CF-HGB-CDs and 0.9 - 3.6 g of aniline monomer and add them to 60 - 240 mL of hydrochloric acid aqueous solution with a concentration of 0.5 - 2 mol / L, ultrasonically disperse for 1 - 4 h, under nitrogen protection, at 0 - 8 °C and continuous stirring, dropwise add ammonium persulfate solution. After the addition is completed, keep stirring and continue the reaction at 0 - 8 °C for 9 - 36 h. After the reaction ends, filter, wash the obtained solid product with 0.01 mol / L hydrochloric acid and acetone in sequence, and vacuum dry at 70 - 90 °C for 6 - 24 h to obtain composite filler: CF-HGB-CDs@PAN.
8. The PVC board with heat insulation, sound insulation and heat preservation functions according to claim 1, wherein The plasticizer is at least one of dioctyl terephthalate, dioctyl phthalate, diisononyl phthalate, trioctyl trimellitate, dioctyl oxalate, triisooctyl trimellitate, bis(2-propylheptyl) phthalate.
9. The PVC board with heat insulation, sound insulation and heat preservation functions according to claim 1, characterized in that, The stabilizer is at least one of calcium stearate, zinc stearate, calcium oleate, zinc oleate.
10. The PVC board with heat insulation, sound insulation and heat preservation functions according to any one of claims 1-9, characterized in that, It is prepared by the following method: Add the raw materials according to the formula components to a kneader, stir and knead at 100 - 125 °C and 300 - 800 rpm for 15 - 30 min, then add it to an open mill, open mill at 115 - 140 °C and 500 - 1000 rpm for 1 - 5 min. Add the obtained mixture to a screw extruder, melt and extrude at 180 - 200 °C. The extruded melt is calendered and formed by a calender, and after peeling and cooling to room temperature, a PVC board with heat insulation, sound insulation and heat preservation functions is obtained.
Citation Information
Patent Citations
High-temperature-resistant high-toughness PVC-U (unplasticized polyvinyl chloride) double-wall corrugated pipe and preparation method thereof
CN104650501A
PVC plate with low moisture absorption and high security and preparation method thereof
CN106566122A
Anti-static PVC composite material and preparation method thereof
CN112175323A
Sound-insulation and heat-insulation composite material and preparation method thereof
CN121450031A
PVC pipe composition with improved noise reduction and flame retardancy and PVC pipes or fittings
KR101952114B1
Cited By
Antistatic flexible connection and preparation method thereof
CN121067151A
Preparation method and system for PVC plate production
CN121133169A